A poetização do espaço nos Sertões de Euclides e Rosa - Santos, Celina Leal dos (2006)
The objective of this survey is to demonstrate the construction of setting in the narratives: Os Sertões, by Euclides da Cunha and Grande Sertão: Veredas, by João Guimarães Rosa. The intention is to elaborate on the following problems: What elements make up the setting in Os Sertões and Grande Sertão: Veredas? How do the multiple settings influence the basic elements of the narrative and vice-versa? In what way could the BACKLANDS take on the grouping effect in Os Sertões and Grande Sertão: Veredas. The studies of Gaston Bachelard, of Antonio Dimas and, thirdly, of Milton Santos will be considered basic to this survey, as well as borrowing from geography. Finally, key-concepts will be extracted, such as the concept of setting, place and landscape. Chapter I deals with the elements of setting that make up Os Sertões; chapter II covers the elements of setting relative to Grande Sertão: Veredas and, following these, chapter III proposes an evaluation of the elements of setting common to both narrative. It also seeks to learn how the BACKLANDS becomes a grouping element of these settings. The backlands is distinguished in this work, as a macro-setting, divided into micro-settings represented by natural elements formed by water, by flora and by fauna. The artificial settings are distinguished by the constructions that revolve around the plantation, the farm, the house, the two-story house, the cabin, the church, the cemetary, and the jail. The point of view of these elements can be either exterior or interior. Thus, this work seeks to rescue aspects of the creation of setting, surrounded in a hybrid discussion of journalism, geology, science, history, sociology and literatura in Os Sertões, as well as latent manifestations of the creation of setting in Grande Sertão: Veredas